In vitro wear behavior of knee implants at different load levels: the impact of the test fluid - Schröder, Stefan; Uhler, Maximilian; Schonhoff, Mareike; Nees, Timo A.; Wonerow, Tanja; Nuppnau, Jens; Mantwill, Frank; Kretzer, Jan Philippe (Lubricants, 2023)
Calf serum is defined as a test fluid for in vitro knee wear simulation studies in the ISO standard. However, protein degradation typically occurs during in vitro wear simulation. The current study should indicate whether increased loads change the rheological properties of the test fluid and may, therefore, lead to favorable tribological behavior and reduced wear. Three different load levels were simulated in a displacement-controlled knee wear simulation study. The gravimetric wear rates were determined, pressure measurements were performed, and the dynamic viscosity of the test fluids were analyzed after the simulation of 0.5 × 106 cycles. The lowest load level led to the lowest wear rate, and the lowest contact pressure and contact area, compared to the medium and high-load level. Although, the high-load level led to the highest contact pressure and contact area, the wear rates were comparable to the medium-load level. The rheological measurements revealed the highest dynamic viscosity for the high-load level and no differences could be found between the medium and low loading condition. To perform realistic wear simulation studies, the reproduction of the in vivo interrelationships between the shear forces and wear are necessary.